Downy Mildew of Lettuce in Florida - Lis Rodrigues Porto; Richard N. Raid; German V. Sandoya (EDIS)
Lettuce Downy Mildew (LDM), caused by the oomycete Bremia lactucae, is the most important disease of lettuce worldwide. LDM has a direct effect on both yield quantity and quality because it may infect lettuce at any growth stage, affecting the marketable portion of the crop. This new 6-page publication of the UF/IFAS Horticultural Sciences Department introduces the LDM disease in Florida lettuce and available control methods and strategies. This publication also introduces the work on LDM in the UF/IFAS Lettuce Breeding Program, which was created to release cultivars adapted to Florida conditions. Written by Lis Rodrigues-Porto, Richard N. Raid, and Germán V. Sandoya. https://edis.ifas.ufl.edu/hs1403